2015
DOI: 10.1039/c5ra09505k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of conjugated/cross-conjugated benzene-bridged boron difluoride formazanate dimers

Abstract: A study designed to probe the effect of electronic conjugation and cross-conjugation on the optical and electrochemical properties of benzene-bridged boron difluoride formazanate dimers is presented. 2 AbstractOne of the most common strategies for the production of molecular materials with optical properties in the far-red/near-IR regions of the electromagnetic spectrum is their incorporation into dimeric architectures. In this paper, we describe the synthesis and characterization ( 1 H, 11 B, 13C and 19 F NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…26 Gilroy and co-workers described similar electrochemical data for these compounds in dichloromethane solution. While the 2-electron reduction products appeared unstable in dichloromethane solution, 25 our data in THF suggest that in this solvent the products are stable and might be isolable (vide infra).…”
Section: Cyclic Voltammetrymentioning
confidence: 73%
See 1 more Smart Citation
“…26 Gilroy and co-workers described similar electrochemical data for these compounds in dichloromethane solution. While the 2-electron reduction products appeared unstable in dichloromethane solution, 25 our data in THF suggest that in this solvent the products are stable and might be isolable (vide infra).…”
Section: Cyclic Voltammetrymentioning
confidence: 73%
“…These compounds were recently reported by Gilroy and co-workers while this manuscript was in preparation. 25 The formation of complexes 1 was confirmed by NMR spectroscopy, which shows diagnostic 1 : 2 : 1 triplets in the 11 B NMR spectra for the 4-coordinate B centres (δ −0.7 to −2.3 ppm). 19 In the 19 F NMR spectra, 1 : 1 : 1 : 1 quartets between −145.6 and −159.4 ppm with J B-F = 20-30 Hz are observed that are consistent with the presence of a BF 2 moiety.…”
Section: Synthesis and Characterisation Of Formazanate Boron Complexesmentioning
confidence: 88%
“…The calculations also revealed that the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) were the dominant orbital pair involved in the lowest energy excitation (*). The HOMO and LUMO isosurfaces ( Figure 2c) are indicative of highly delocalized electronic structures and closely resemble those of related boron difluoride formazanate complexes, [62][63] with minor orbital contributions located on the oxygen atoms of the phosphine oxide donors. The lack of frontier orbital density on the phosphorus atoms and their substituents are consistent with the experimental observation that the phosphine oxide donors have a negligible effect on the low-energy absorption maxima of the aluminum complexes described here.…”
Section: Uv-vis Absorbance Spectroscopymentioning
confidence: 73%
“…Several examples of 1,2‐bis((1 H ‐pyrrol‐2‐yl)methylene)hydrazines (BOPHYs) 5 and 8‐imidazodipyrromethenes ( aza ‐BOIMPYs) 6 exhibit exceptional Φ em in dilute solutions due to their relatively planar and rigid molecular geometries. BF 2 formazanate dimers 7 a and 7 b undergo emission enhancement upon dimerization at both the meta and para positions of the phenylene linkers . BODIPY dimers (e.g., 8 and 9 ) exhibit twisted‐intramolecular charge transfer in polar solvents, which is responsible for a decrease in the emission quantum yield …”
Section: Introductionmentioning
confidence: 99%